2006
DOI: 10.1161/01.atv.0000214960.85469.68
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Oxidation Protein Products Accelerate Atherosclerosis Through Promoting Oxidative Stress and Inflammation

Abstract: Objective-Increased level of plasma advanced oxidation protein products (AOPPs) has been found in patients with uremia and nonuremic subjects with coronary artery disease. This study was conducted to test the hypothesis that AOPPs play a causal role in atherosclerosis. Methods and Results-Hypercholesterolemic (0.5% wt/wt diet) or normal rabbits received either repeated intravenous injections of AOPPs modified rabbit serum albumin (AOPPs-RSA) or unmodified RSA for 8 weeks. Compared with RSA-or vehicle-treated h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
114
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(122 citation statements)
references
References 32 publications
5
114
0
3
Order By: Relevance
“…As a further indication of the validity of the HFHC diet (with 3% cholesterol) applied by us, the rats in our study showed obesity as well as hyperlipidemia and steatohepatitis (DimitrovaShumkovska et al, 2010a). Parameters for enhanced oxidative stress, as we detected in plasma of our HFHC rats may correlate with inflammatory processes, including atherogenic effects observed by us and others (Witko-Sarsat et al, 1998;Liu et al, 2006;Dimitrova-Shumkovska et al, 2010a). In particular the high AOPP levels observed in the liver, plasma, and aorta, as induced by the HFHC diet, may present factors reflecting liver pathology and atherogenesis (Watanabe et al, 2004;Oettl et al, 2008;Dimitrova-Shumkovska et al, 2010a).).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…As a further indication of the validity of the HFHC diet (with 3% cholesterol) applied by us, the rats in our study showed obesity as well as hyperlipidemia and steatohepatitis (DimitrovaShumkovska et al, 2010a). Parameters for enhanced oxidative stress, as we detected in plasma of our HFHC rats may correlate with inflammatory processes, including atherogenic effects observed by us and others (Witko-Sarsat et al, 1998;Liu et al, 2006;Dimitrova-Shumkovska et al, 2010a). In particular the high AOPP levels observed in the liver, plasma, and aorta, as induced by the HFHC diet, may present factors reflecting liver pathology and atherogenesis (Watanabe et al, 2004;Oettl et al, 2008;Dimitrova-Shumkovska et al, 2010a).).…”
Section: Discussionsupporting
confidence: 68%
“…However, protein oxidation products have been found in the extracellular matrix of human and animal atherosclerotic plaques (Woods et al, 2003;Li et al, 2007). The study by Liu et al (2006) was the first to our knowledge to provide in vivo evidence for a causal relationship between chronic AOPPs accumulation and atherosclerosis. This research suggests that increases in plasma AOPP, particularly in a hypercholesterolemic environment, accelerate atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of AOPP may accelerate ox-LDL formation through enhanced OS, increased plasma TNF-α and other inflammatory mediators, enhanced macrophage invasion and smooth muscle cell proliferation in the arterial wall. Plasma AOPP elevation significantly increases atherosclerotic plaque in hypercholesterolemic rabbits and accelerates progression of atherosclerosis 30 . Of particular clinical importance is the finding that AOPPs are highly correlated with carotid intima media thickness in end-stage renal disease 31 and in peritoneal dialysis patients 32,33 .…”
Section: Discussionmentioning
confidence: 97%
“…It was well demonstrated that AOPPs could induce ROS generation via the activation of NADPH oxidase. (Kalousova et al., 2002; Liu et al., 2006; Weinstein & Manolagas, 2000; Witko‐Sarsat et al., 1996; Wu et al., 2016; Xie et al., 2014). We found that AOPPs could activate the NADPH oxidase and significantly increase ROS production in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%